Relationship of Adipocyte binding protein with insulin resistance in Type II Diabetes mellitus (Journal of Pharmaceutical Negative Results, 2022)
Background: Adipocyte binding protein (ABP) is an adipokine hormone, although its association with insulin resistance remains elusive, and the underlying mechanism are also unknown. The aim of the present study is to investigate the possible association between RBP4 with blood glucose, glycated hemoglobin (HbA1C) in diabetes mellitus (DM) with insulin resistance. Methods: in this study 45 apparently healthy subjects in both sexes their ages were 50-70 years and 44 subjects with DM type II were taken. Anthropometric parameters (weight, height, body mass index (BMI) and waist circumference (WC) ) were measured. Furthermore, serum RBP4, homeostatic association model of insulin resistance (HOMA IR), homeostatic association model of b-cell function (HOMA B), blood glucose, HbA1C, and liver function tests were measured. Results: serum RBP4 was significantly reduced in type II DM compared with the control group, and according to the receiver operating characteristic (ROC) curve, the RBP4could be representing as biomarker for DM type II. The WC in DM type II was lower than non-diabetic subjects. On the other hand, the BMI were not differ between two studied groups. Interestingly, the result showed that HOMA IR and HbA1C were markedly increased in diabetic subjects as compared to the non-diabetic group, and their ROC were 0.8 and 0.96, respectively, which means a very good indicator marker for severity of DM. In addition, serum alanine aminotransferase (ALT) and alkaline phosphates (ALP) significantly increased in type II DM as compared with the control group. However, aspartate aminotransferase (AST) represented as an excellent biomarker for DM complications but with no change. Statistical analysis showed that RBP4 was negatively correlated with the blood glucose, HbA1C, HOMA IR and HOMA B. Conclusions: The current study, and for the first time the obtained result suggested that serum RBP4 could be represented as a new biomarker for DM type II because it is negatively associated with the insulin resistance markers.